Early medieval glosses on Prudentius' Psychomachia : the Weitz tradition - O'Sullivan, Sinéad (Mittellateinische Studien und Texte ;, 2004)
This book focuses on the glosses on Prudentius' Psychomachia as found in the German or Weitz manuscript tradition. These glosses provide a fascinating window to the intellectual world of the late Carolingian and Ottonian periods. Introducing the reader to the rudiments of Christian exegesis and encyclopaedic information, they represent an important moment in the history of early medieval thought and instruction. In the book attention is redirected from the philological concerns of conventional glossing studies toward mainstream intellectual history. The first part examines the manuscripts, function and sources of the glosses. The second part provides an introduction to the edition, together with a diplomatic transcription of the Latin and German annotations in three Weitz manuscripts.